Transformasi Tata Kelola Pemerintahan Desa Berbasis Digital dalam Pemberdayaan UMKM untuk Meningkatkan Kesejahteraan Ekonomi Masyarakat di Desa Sukaratu Kec. Sukaratu Kab. Tasikmalaya - Iis Miati; Yanti Heryanti; Rudi Setiawan; Cica Yulianti; Hirdy Hari Qatari; Syam Satria Falah; Muhamad Ikhsan Mulyana; Arga Ilmansah; Febrian Nur Apriliani; Nadya Radeva Mumtaza; Sara Uswatun Zakiyah; Abdel Gebi Genaldi; Yessy Intan Febianeu Indah Sari; Wulan Dari; Nizar Prabawa (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Digital transformation is one way to improve the quality of village government management, especially in handling data for small, medium, and micro businesses. This community service aims to develop and implement a small business information system in Sukaratu Village, Sukaratu Subdistrict, Tasikmalaya Regency, as a way to help manage integrated and digital data. The method used involves coordination, observation, interviews, collecting data from small and medium enterprises, developing a system, training, implementation, guidance, and evaluation, which includes lecturers and students from the KKN program in the study programs of Public Administration and Business Administration. The results of the activity show that the UMKM Information System has made data management more effective, sped up the data collection and report creation process, and created a more accurate and well-organized UMKM database. In addition, training and support help village officials improve their ability to use the system, which makes it easier for them to implement data-based governance. The implementation of the system is expected to serve as a foundation for strengthening more effective, transparent, and accountable village government management, as well as supporting sustainable planning for development and empowerment of small and medium enterprises.